Analisis Kinerja Keuangan Dengan Menggunakan Metode Common Size Pada Sub Sektor Footwear - Farah Nugraheny P; Puji Muniarty Puji (Pascasarjana STIE Amkop Makassar, 2022)
This study aims to determine the analysis of financial performance using the Common Size method at PT. Primarindo Asia Infrastructure, Tbk and PT. Sepatu Bata, Tbk listed on the Stock Exchange as seen from the financial statements in the form of a balance sheet and profit and loss. This type of research is descriptive with a quantitative approach. Documentation data collection techniques and literature study. Data analysis technique using Common Size analysis and one sample test. The research data consists of Current Assets, Debt and Net Profit at PT. Primarindo Asia Infrastructure Tbk and PT. Sepatu Bata, Tbk. The sampling technique uses purpose sampling. The results showed that the financial performance by using a common size: (a) PT. Primarindo Asia Infrastructure, Tbk through total current assets performed well than expected (b) PT Primarindo Asia Infrastructure, Tbk through total debt performed less well than expected (c) PT. Primarindo Asia Infaktur, Tbk through the total net profit performed well than expected (d) PT. Sepatu Bata, Tbk through total current assets performed well than expected (e) PT. Sepatu Bata, Tbk through total debt underperforming less than expected (f) PT. Shoes Bata, Tbk through its total net income did not perform well than expected